5a-a*a+[5a*a-3a]-6*[a*a-a]
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 03:53:17
5a-a*a+[5a*a-3a]-6*[a*a-a]5a-a*a+[5a*a-3a]-6*[a*a-a]5a-a*a+[5a*a-3a]-6*[a*a-a]原式=5a-a^2+5a^2-3a-6*(a
5a-a*a+[5a*a-3a]-6*[a*a-a]
5a-a*a+[5a*a-3a]-6*[a*a-a]
5a-a*a+[5a*a-3a]-6*[a*a-a]
原式=5a-a^2+5a^2-3a-6*(a^2-a)
=5a-a^2+5a^2-3a-6a^2+6a
=8a-2a^2
注:a^2=a的平方
5a-a×a+[5a×a-3a]-6×[a×a-a]
=-4a-2a²
“匿名网友41”正确,答案8a-2a*a,过程可完全参考“匿名网友41”的
5a-a*a+[5a*a-3a]-6*[a*a-a]
a-2a+3a-4a+5a-6a+...+99a-100a
化简; a-2a+3a-4a+5a-6a+``````-2006a+2007a.
(a+3a+5a+...+2009a)-(2a+4a+6a+...+2008a)=
(a+3a+5a+.+2009a)-(2a+4a+6a+.2008a)
计算(a+3a+5a+...+2009a)-(2a+4a+6a+...+2010a)
(a+3a+5a+...+2013a)-(2a+4a+6a+...+2012a)=
化简:a-2a+3a-4a+5a-6a+.+2010a+2011a.
计算(a+3a+5a+.+2003a)-(2a+4a+6a+...+2004a)
(a+3a+5a+.+2003a)-(2a+4a+6a+.+2004a)
(a+3a+5a...+2009a)-(2a+4a+6a+...+2010a)=?
a+a+1+a+2+a+3+a+4+a+5+a+6+a+7.+a+2013+a+2014=?
a-2a+3a-4a+5a-6a+7a-8a+9a-10a+11a.+99a-100a=
a=-1 求a-2a+3a-4a+5a-6a+...+99a-100a
9a*a*a*a-()=(3a*a+5c)(3a*a-)
5a^-〔a^-2a-2(a^-3a)]
(a+3a+ 5a+```+2007a)-(2a+4a+6a+```+2008a)=?(a+3a+ 5a+```+2007a)-(2a+4a+6a+```+2008a)等于多少?写出过程和代数式,
合并同类项:a-2a-3a+4a+5a-6a-7a+8a+9a-10a-11a+12a+……+2008a+2009a-2010a-2011a